1992
DOI: 10.1136/jmg.29.10.742
|View full text |Cite
|
Sign up to set email alerts
|

A male with trisomy 9 mosaicism and maternal uniparental disomy for chromosome 9 in the euploid cell line.

Abstract: We describe a 17 year old male with a low level of trisomy 9 mosaicism. Maternal uniparental chromosome 9 disomy in the euploid cell line was shown to have arisen after postzygotic loss of the paternal chromosome 9 from the trisomic cell line by cytogenetic and molecular analysis. This is believed to be the first report of uniparental disomy for chromosome 9.In four of the 11 reported cases of mosaic trisomy 9 syndrome, including our patient, a maternally derived pericentric inversion of the heterochromatic ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 4 publications
2
36
0
Order By: Relevance
“…Kaiser (1984) has summarized the following interesting observations from the analysis of 72 reported cases, i) Breakpoint specificity and clustering; of the 72 reported cases 56 were of type I, 4 of type II, 3 of type III, and 5 of uncommon types (one case each), ii) Occurrence and recombination; all cases of common types were of familial occurrence without recombination of chromosome 9, contrasting to 1 case of de novo mutation and 3 cases of recombinants out of 5 cases with uncommon breakpoin~s. ~ii) Segregation in family members; the segregation pattern was not different from the: expected distribution of 1:1. iv) Spermatogenesis; apparently normal histology of testes and normal pairing with the exception of the inverted segment reported in 3 carrier males, v) Predisposition to nondisjunction; out of 10 patients with mosaic trisomy 9 reported, 5 were found to have inv(9) which was double in trisomic cells and of maternal origin in all the cases (Willatt et al, 1991).…”
Section: Discussionmentioning
confidence: 98%
“…Kaiser (1984) has summarized the following interesting observations from the analysis of 72 reported cases, i) Breakpoint specificity and clustering; of the 72 reported cases 56 were of type I, 4 of type II, 3 of type III, and 5 of uncommon types (one case each), ii) Occurrence and recombination; all cases of common types were of familial occurrence without recombination of chromosome 9, contrasting to 1 case of de novo mutation and 3 cases of recombinants out of 5 cases with uncommon breakpoin~s. ~ii) Segregation in family members; the segregation pattern was not different from the: expected distribution of 1:1. iv) Spermatogenesis; apparently normal histology of testes and normal pairing with the exception of the inverted segment reported in 3 carrier males, v) Predisposition to nondisjunction; out of 10 patients with mosaic trisomy 9 reported, 5 were found to have inv(9) which was double in trisomic cells and of maternal origin in all the cases (Willatt et al, 1991).…”
Section: Discussionmentioning
confidence: 98%
“…Willatt et al (1992) observed that, in 11 reported cases of the rare mosaic trisomy 9 syndrome, 4 occurred in the setting of maternal heterozygosity for the inv(9)(p11q12) variant, suggesting a causal link. Partial trisomy 9 has been associated with a parental inv(9)(p11q12/3) (Kaiser 1984;Stamberg and Thomas 1986).…”
Section: Discussionmentioning
confidence: 99%
“…As might be expected, the majority were of homozygosity for pericentric inv (9). 21,23,[35][36][37][38][39][40][41][42][43] However, reports of homozygosity for pericentric inv(2), 44 inv(4), 45 inv(3) 46 and also for a paracentric inv(12) 47 also exist. Analysis of mode of inheritance showed various patterns of origin and ascertainment.…”
Section: Robertsonian Translocationsmentioning
confidence: 86%
“…23,[39][40][41][42] In case 30, where the mother was heterozygous for inv (9), and the father of normal karyotype, the homozygosity and accompanying low level of trisomy 9 mosaicism was determined to be due to uniparental disomy with all copies of this chromosome being of maternal origin. 43 Ascertainment for inv(9) homozygosity was made after prenatal diagnosis in four cases (18, 19, 26 and 27), most commonly after routine amniocentesis for advanced maternal age. In these instances, the homozygotes were phenotypically normal.…”
Section: Robertsonian Translocationsmentioning
confidence: 99%